Recent trends in algebraic development techniques : 24th IFIP WG 1.3 International Workshop, WADT 2018, Egham, UK, July 2-5, 2018, Revised selected papers /: 24th IFIP WG 1.3 International Workshop, WADT 2018, Egham, UK, July 2-5, 2018, Revised selected papers. (2019) - Unknown
No abstract available